Światło Paschy w liturgii jerozolimskiej pierwszych wieków - Bać, Tomasz (Verbum Vitae, 2016)
This article examines the relevance and the significance of the symbol of the light in the paschal liturgy in Jerusalem in the first millennium. The rite of the lighting the candle, which opens the liturgy of the Easter Vigil (called the Easter Lucernarium), is present in all the known sources of the Jerusalem liturgy. The most significant of these are Itinerarium Egeriae (end of the 4th century), the Armenian Lectionary (5th century), the Grand Lectionary of the Church of Jerusalem from the Georgian tradition (6th-8th century) and the Typicon of the Anastasis (12th century). The development of the rite of paschal light – which includes the lighting of the candle or candles inside of the chapel of the Tomb of Christ, passing the fire to the whole congregation, prayers, psalms, antiphons and processions – reflects the profound theological significance of the Resurrection of Christ. Indeed, the celebration of Easter in Jerusalem, thanks to the very evocative symbol of light, has always been preeminent among Christological and ecclesiological event.